A filter less improved control scheme for active/reactive energy management in fuel cell integrated grid system with harmonic reduction ability. (15th April 2022) - Tanzim Meraj, Sheikh; Zaihar Yahaya, Nor; Hasan, Kamrul; Hossain Lipu, M.S.; Madurai Elavarasan, Rajvikram; Hussain, Aini; Hannan, M.A.; Muttaqi, Kashem M.
Highlights: A fuel cell integrated grid system for active/reactive energy management is proposed. A filter-less PQ (FLPQ) control scheme is developed to achieve optimum energy flow. FLPQ has improved power quality with better transient response. FLPQ reduces the cost for the consumers and any additional power losses. Abstract: Fuel-cell integrated electrical grid systems are considered the future of energy generation since it is highly energy-efficient and environmentally friendly. However, they are still in the initial phase of implementation and hold some drawbacks that need to be addressed. In fuel cell integrated grid systems, electrical loads usually produce active/reactive power which hampers the nominal operation of the grid system and depreciates the power factor of the system. This condition instigates massive energy loss in the system by generating harmful harmonic components. It also increases the energy demand and thus, the consumers are penalized with excessive bills. The conventional energy management systems in a fuel cell-based grid usually incorporate conventional power filters which are incapable of accurately eliminating harmonic components and unable to compensate reactive power generated by the local loads. Thus, these control systems cannot properly compensate for the energy flow in the grid. To deal with this issue, the current manuscript proposes a new filter-less active/reactive energy management approach that can compensate for reactive powers by accurately eliminating harmonics from the grid system. In this manner, the proposed system can prevent energy loss and enables the consumers to save up on electricity bills. The performance of the proposed system is analyzed under different load conditions and the results are compared with other conventional energy management schemes to verify its superiority. The results from the case studies showed that the proposed control can effectively reduce harmonics from the system and can also keep the power factor of the grid system close to unity.